2018
DOI: 10.1590/1678-4324-2018180225
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Epidemiological Factors and Cognitive Impairment: A Cross-Sectional Study in the Elderly Population

Abstract: Purpose Population aging is one of the great achievements of humanity. However, with aging, the incidence of chronic diseases and those related to cognition deficits increase. In this way, strategies aimed at preventing or delaying cognitive deficit are extremely necessary. Thus, this study investigates the relationship between cognitive deficits, schooling and eating habits in a Brazilian elderly population. Methods The dietary habits of 400 older adults were investigated through structured questionnaires. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…After reviewing full texts, one record written in Japanese, four records with overlapping studies, two ecological studies, three records with changes of brain structure or β-amyloid (Aβ) deposit as outcomes, and eight records combining meat, fish, and other food together as exposures were excluded, including one paper with an unclear description on meat by Heys et al (2010) [23] without any reply from two authors contacted. Therefore, twenty-nine eligible records were included in the review: twelve cohort [9][10][11][24][25][26][27][28][29][30][31][32], three case-control [33][34][35], thirteen cross-sectional studies [36][37][38][39][40][41][42][43][44][45][46][47][48], and one intervention study [49] (Figure 1). Egger's regression model to detect small-study effects (P < 0.05).…”
Section: Characteristics Of Studies and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing full texts, one record written in Japanese, four records with overlapping studies, two ecological studies, three records with changes of brain structure or β-amyloid (Aβ) deposit as outcomes, and eight records combining meat, fish, and other food together as exposures were excluded, including one paper with an unclear description on meat by Heys et al (2010) [23] without any reply from two authors contacted. Therefore, twenty-nine eligible records were included in the review: twelve cohort [9][10][11][24][25][26][27][28][29][30][31][32], three case-control [33][34][35], thirteen cross-sectional studies [36][37][38][39][40][41][42][43][44][45][46][47][48], and one intervention study [49] (Figure 1). Egger's regression model to detect small-study effects (P < 0.05).…”
Section: Characteristics Of Studies and Quality Assessmentmentioning
confidence: 99%
“…The mean age of participants was more than 60 years except for two studies, one with a mean age of 52.9 years [46] and one with a range of 40-65 years [43]. Of twenty-nine eligible studies, twenty-four measured consumption of total meat based on a food frequency questionnaire (FFQ) and/or dietary records; one study reported consumption of beef and pork as the exposure [33]; one specified frequencies of use of red meat and sausages as the exposure [31]; two investigated whether participants had habitual intake of red meat with fat or chicken with skin (yes/no) [45,48]; and one intervention study used pork-containing meals as the exposure [49]. Among the studies included, five of them used Alzheimer's disease and/or dementia as outcomes [24,25,33,39,47], twenty-three measured cognitive function via one or a series of cognitive tests, and one reported both AD and cognitive function [31].…”
Section: Characteristics Of Studies and Quality Assessmentmentioning
confidence: 99%
“…When comparing total milk, semi-skim/skim and full-fat milk intakes where the only difference between products was the lipid content, de Goeij et al ( 22 ) found no associations with any cognitive domain scores. In support of this, there were no differences in cognitive function between those consuming skim vs. full-fat milk in a study based in Brazil ( 38 ).…”
Section: Observational Studiesmentioning
confidence: 79%
“…Some studies found positive associations between dairy lipid intake ( 26 ), and some found no association ( 22 , 27 ). The results may have been confounded by the inclusion of fermented dairy products in the analysis because studies that solely assessed low-fat vs. full-fat milk consumption found no difference in cognitive outcomes ( 22 , 38 ). The consumption of high-fat dairy desserts was reported to be a risk factor for cognitive impairment ( 37 ); however, this was not necessarily due to the lipid intake and could instead be attributed to the high sugar content of the desserts.…”
Section: Discussionmentioning
confidence: 99%
“…Pastor-Valero et al found out that individuals with cognitive impairment significantly eat less fruit and vegetables ( p < 0.001) and fish ( p < 0.001) compared to subjects without cognitive impairment [ 14 ]. According to França et al, participants who ate fewer vegetables (4 times per week) were 47.6% more likely to develop a cognitive deficit (OR: 0.524; 95% CI: 0.310–0.877; p = 0.045) [ 26 ]. Lastly, consuming < 5 servings /day of fruits and vegetables was positively associated with suspected cognitive impairment (OR: 2.02; 95% CI: 1.05–2.99; p = 0.048), as reported by Martinez et al [ 27 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%